Zirconium(IV) and hafnium(IV) coordination polymers with a tetra-acetyl-ethane (Bisacac) ligand: Synthesis, structure elucidation and gas sorption behavior. (29th March 2015) - Hentschel, Felix; Vinogradov, Vladimir V.; Vinogradov, Alexandr V.; Agafonov, Alexander V.; Guliants, Vadim V.; Persson, Ingmar; Seisenbaeva, Gulaim A.; Kessler, Vadim G.
Graphical abstract: Pseudo crystalline coordination polymer complexes of Zr(IV) and Hf(IV) cations with tetra-acetyl-ethane (Bisacac) ligand have been successfully produced in high yields and their structures were elucidated using EXAFS studies. The obtained materials display highly temperature dependent gas sorption behavior. Highlights: Octahedrally shaped crystals of Zr(Bisacac)2 and Hf(Bisacac)2, were obtained in quantitative yields. Molecular structures of the obtained pseudo crystalline coordination polymers were determined with the help of EXAFS spectroscopy. Produced coordination polymers adsorbed hydrogen reasonably well at 77 K but almost not at all 293 K. Abstract: Octahedrally shaped crystals of Zr(Bisacac)2 and Hf(Bisacac)2, M(IV) derivatives of bis-acetylacetone (tetra-acetyl-ethane), H2 Bisacac, were obtained in quantitative yield by a simple and reproducible synthetic procedure. The coordination spheres of Zr and Hf were found to be very closely related to those in molecular beta-diketonates, M(acac)4, according to the data of EXAFS spectroscopy. The structures are highly disordered, reflecting the multitude of conformations possible for each M(IV) centre. Crystal structure models involving metal centres with tetrahedrally arranged binding nodes were proposed for M(Bisacac)2 . The produced materials are microporous with pronounced temperature-dependent affinity and selectivity to hydrogen gas absorption.